2020
DOI: 10.1038/s41598-020-69958-0
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular vancomycin powder is effective in preventing infections following total hip and knee arthroplasty

Abstract: Locally applied vancomycin is increasingly being used in primary hip and knee arthroplasty to reduce the risk of infection. Despite encouraging initial results, considerable debate remains on the basis of the data currently available. In particular, it has been unclear up to now whether local vancomycin is suitable to further reduce the risk of infection even if the rate of infection is already low (< 1%). In this monocentric retrospective cohort study, all primary total hip and knee arthroplasties performed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…The vancomycin powder initially demonstrated high concentrations in the effluent but was steadily and rapidly washed out so that after two hrs it was below detection limits by LCMS (Figure 3A) and failed to produce a zone of inhibition (Figure 6A). Recently, intraarticular placement of vancomycin powder has been used in primary knee and hip arthroplasty [26]. Otte et al reported intrawound placement of vancomycin reduced infection [14] however other studies have shown that vancomycin powder had no effect on preventing infection [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The vancomycin powder initially demonstrated high concentrations in the effluent but was steadily and rapidly washed out so that after two hrs it was below detection limits by LCMS (Figure 3A) and failed to produce a zone of inhibition (Figure 6A). Recently, intraarticular placement of vancomycin powder has been used in primary knee and hip arthroplasty [26]. Otte et al reported intrawound placement of vancomycin reduced infection [14] however other studies have shown that vancomycin powder had no effect on preventing infection [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a major retrospective study by Matziolis et al 20 evaluated the use of intra-articular VP in 8,945 cases of total joint arthroplasty. Vancomycin powder was used in 1082 joints.…”
Section: Discussionmentioning
confidence: 99%
“…In a single center study of 98 patients, Aljuhani et al did not find a significant difference in infection rates after primary TKA when using intrawound VP 24 . In a separate retrospective cohort study of patients undergoing TKA and THA, Matziolis et al found that although a small difference in PJI risk was observed in the group with local vancomycin compared with the control group, it was not statistically significant 25 .…”
Section: Total Hip Arthroplasty and Total Knee Arthroplastymentioning
confidence: 96%